Investigation of Amplitude and Phase Distortions in DAB System - Meister, A.; Lossmann, E.; Martverk, P. (Elektronika ir Elektrotechnika, 2000)
Effects of signal amplitude and phase distortions occurring in case of multipath propagation of digital audio broadcasting (DAB) signal are discussed. Symbol error probabilities depending on relative attenuation of reflected beams and signal-to-noise ratio are calculated.